Astrocyte-Secreted Factors Selectively Alter Neural Stem and Progenitor Cell Proliferation in the Fragile X Mouse - Sourial, Mary; Doering, Laurie C. (Frontiers in Cellular Neuroscience, 2016)
An increasing body of evidence indicates that astrocytes contribute to the governance and fine tuning of stem and progenitor cell production during brain development. The effect of astrocyte function in cell production in neurodevelopment disorders is unknown. We used the Neural Colony Forming Cell assay to determine the effect of astrocyte conditioned media (ACM) on the generation of neurospheres originating from either progenitor cells or functional stem cells in the knock out (KO) Fragile X mouse model. ACM from both normal and Fmr1-KO mice generated higher percentages of smaller neurospheres indicative of restricted proliferation of the progenitor cell population in Fmr1-KO brains. Wild type neurospheres, but not KO neurospheres, showed enhanced responses to ACM from the Fmr1-KO mice. In particular, Fmr1-KO ACM increased the percentage of large neurospheres generated, representative of spheres produced from neural stem cells. We also used 2D DIGE to initiate identification of the astrocyte-secreted proteins with differential expression between Fmr1-KO and WT cortices and hippocampi. The results further support the critical role of astrocytes in governing neural cell production in brain development and point to significant alterations in neural cell proliferation due to astrocyte secreted factors from the Fragile X brain.